Product quality and cafe atmosphere perspectives on fore coffee customer satisfaction - Philemon Tiovan Siambaton Munthe; Helma Malini; Nur Afifah; Bintoro Bagus Purmono; Harry Setiawan (International Journal on Social Science, Economics and Art, 2023)
There are currently a lot of coffee shops in Indonesia, and they are effortless to find. Coffee drinks, which were previously only enjoyed by adults, have now become drinks that are much sought after by young people. Young people consider product quality and an attractive and comfortable atmosphere when choosing which coffee shop to visit. This quantitative research goals to determine the influence of product quality and cafe atmosphere on customer satisfaction fore coffee through brand image as an intervening variable. 200 participants from several major Indonesian islands participated in this study; they were gathered online using a purposive sample approach and a questionnaire. Data were analyzed using Structural Equation Modeling (SEM) using AMOS 24. This research shows that product quality positively and significantly affects brand image. Product quality also has a positive and significant effect on customer satisfaction. Likewise, the cafe atmosphere positively and significantly affects brand image. In contrast to the cafe atmosphere, it has a negative and insignificant effect on customer satisfaction. Brand image has an indirect influence on product quality and customer satisfaction. The Brand image also indirectly influences the cafe atmosphere and customer satisfaction. These findings can help coffee shop business actors strengthen their competitiveness in the current era of intense coffee shop competition.